'Head in the Clouds and Feet in the Mud': The role of private universities in the integration of Christian Mission and Transformational Development. - Schultheis, Michael (Transformation (02653788), 2005)
Discusses the role of private universities in the integration of Christian mission and transformational development. Impact of the knowledge-based economy on education; Crisis of higher education in Africa and the growth of private universities; Higher education and Christian churches in Africa; Catholic university of Ghana; Catholic university of Mozambique; Directions for the future.